Developmental aspects of maternal-fetal, and infant gut microbiota and implications for long-term health. Issue 1 (December 2015) - Neu, Josef
Abstract Background Early life interactions between the human host and microbes set the stage for future health and disease. Findings In this review, some of the relationship of the human microbiome effects will be discussed as they relate to preterm delivery, early life diseases seen in prematurely delivered infants, and other childhood and adult maladies which include autoimmunity, allergic diseases, obesity or a healthy phenotype. Conclusion Although the data in these areas is just beginning to emerge, this review will provide a brief summary of some of the key research being done and will also speculate on emerging areas where major questions are being raised.